2021
DOI: 10.1097/pr9.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional health changes after a multimodal pain rehabilitation program: a registry-based study

Abstract: Supplemental Digital Content is Available in the Text. A third of patients improved simultaneously in several domains, and a third improved in few or none. Pain intensity was the least likely outcome to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Both groups showed an overall tendency for improvement in the PROMs, namely, self-reported anxiety, depression and EQ5D, especially at the one-year follow-up, although some changes did not reach statistical significance. The effect of IPRP on these PROMs is in line with previous studies evaluating the effect of IPRP [ 10 , 45 ]. The patients who received the DAP intervention showed significant improvements in sleep, both at the post-rehabilitation follow-up and at the one-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both groups showed an overall tendency for improvement in the PROMs, namely, self-reported anxiety, depression and EQ5D, especially at the one-year follow-up, although some changes did not reach statistical significance. The effect of IPRP on these PROMs is in line with previous studies evaluating the effect of IPRP [ 10 , 45 ]. The patients who received the DAP intervention showed significant improvements in sleep, both at the post-rehabilitation follow-up and at the one-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…The complexity of the disorder also raises the question of which parameters one can expect to be affected by a rehabilitation programme. A recent study found that pain intensity was one of the factors with the least probability of improvement, whilst depression was the factor with the highest probability of improvement in patients after participating in an IPRP in Sweden [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies on predictive factors in accordance with the ones presented here regarding a patient population with chronic, severe pain who has completed a similar one-to-one, physiotherapist-led rehabilitation program. Various patient-populations with various severeness of symptoms have been studied, various content of rehabilitation programs have been used, and the studies have been performed in various health care settings in specialized and in primary care [20,23,[40][41][42][43][44][45][46][47][48][49][50][51]. Moreover, the previous literature shows somewhat conficting results of that; no strong predictive baseline variables exist to predict successful outcome [20-23, 42, 46, 47], and worse baseline status can be associated with improved outcome after rehabilitation [23,40,42,[46][47][48], but also that poor pretreatment physical and psychological functioning at the baseline can have a negative prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Various patient-populations with various severeness of symptoms have been studied, various content of rehabilitation programs have been used, and the studies have been performed in various health care settings in specialized and in primary care [20,23,[40][41][42][43][44][45][46][47][48][49][50][51]. Moreover, the previous literature shows somewhat conficting results of that; no strong predictive baseline variables exist to predict successful outcome [20-23, 42, 46, 47], and worse baseline status can be associated with improved outcome after rehabilitation [23,40,42,[46][47][48], but also that poor pretreatment physical and psychological functioning at the baseline can have a negative prognosis [20]. Also, in previous studies, various outcomes and predictive baseline variables are used [20,23,[40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…For fibromyalgia, OMERACT 2 and others have suggested preliminary responder criteria based on several variables [38][39][40]. A similar approach that defines a total improvement variable based on the dichotomizing six variables was used by Grimby-Ekman et al [41].…”
Section: How To Evaluate the Complex Iprp Interventionmentioning
confidence: 99%